Phase-I trial of survivin inhibition with EZN-3042 in dogs with spontaneous lymphoma - Thamm, Douglas H. (BMC Vet Res, 2020)
BACKGROUND: Lymphoma is a common cancer in dogs. While most dogs receiving chemotherapy experience remission, very few are cured, and median survival times are generally in the 12-month range. Novel approaches to treatment are unquestionably needed. The Inhibitor of Apoptosis Protein (IAP) family member survivin, which is one of the most commonly overexpressed proteins in human cancer, plays a key role in apoptosis resistance, a major cause of drug-resistant treatment failure. Survivin targeting therapies have shown promise preclinically; however, none have been evaluated in dogs to date. The goal of the current study was to determine the safety and pharmacodynamic effects of systemic administration of the anti-survivin locked nucleic acid antisense oligonucleotide EZN-3042 in dogs with lymphoma. RESULTS: We performed a prospective phase-I clinical trial in dogs with biopsy-accessible peripheral nodal lymphoma. Eighteen dogs were treated with EZN-3042 as a 2-h IV infusion at 5 dose levels, from 3.25 to 8.25 mg/kg twice weekly for 3 treatments. No dose-limiting toxicities were encountered. Reduction in tumor survivin mRNA and protein were observed in 3 of 5 evaluable dogs at the 8.25 mg/kg dose cohort. CONCLUSIONS: In conclusion, reduced survivin expression was demonstrated in lymphoma tissues in the majority of dogs treated with EZN-3042 at 8.25 mg/kg twice weekly, which was associated with minimal adverse effects. This dose may be used in future studies of EZN-3042/chemotherapy combinations in dogs with spontaneous lymphoma and other cancers.